Manufacturing of novel oxygen carriers for chemical-looping combustion - Richard, Ian (My University, 2011)
Chemical looping combustion is an emerging technology used to produce energy along with intrinsic carbon dioxide separation. It is a process in its very early stages, but is supported by very high carbon dioxide capture rates and efficiencies, as well as versatility for use with a variety of different fuels. This indicates that CLC is an economically viable alternative to the processes currently in use. Unlike processes commonly used today, the exit stream does not contain unwanted flue gases such as nitrogen, but consists only of carbon dioxide and water. Once the water is removed, a pure stream of CO2 is obtained, gas which otherwise would have released to the atmosphere. This can be done due to the presence of an oxygen carrier in the system. This oxygen carrier is in the form of metal oxide particles which acts as a bed material circulating between two fluidised bed reactors. In the air reactor, oxygen is transferred from the combustion air to the oxygen carrier and in the fuel reactor the oxygen carrier transfers oxygen to the fuel, driven by the gas velocity in the air reactor. It is important to consider the characteristics of the metal oxide when finding an appropriate oxygen carrier material. Sufficient rates of oxidation and reduction are required along with enough strength to limit particle breakage and attrition. It would also be advantageous if the material was environmentally friendly and cheap. The focus of this work was on the in-house production of these metal oxide particles. Specifically, on the method followed to produce oxygen carrier materials using conventional laboratory equipment. A number of metal oxides were produced using alumina, ceria and gadolinium-doped ceria as support materials, tested and analysed. It was confirmed through X-ray diffractometry (XRD) that, generally the desired materials were successfully manufactured.
Keywords: Energi; Hållbar utveckling; Oorganisk kemi; Kemisk energiteknik; Energy; Sustainable Development; Inorganic Chemistry; Chemical energy engineering